Analysis of factors affecting radiation exposure during percutaneous nephrolithotomy procedures. (27th June 2019) - Balaji, Sudharsan S.; Vijayakumar, Mohankumar; Singh, Abhishek G.; Ganpule, Arvind P.; Sabnis, Ravindra B.; Desai, Mahesh R.
Abstract : Objectives: To measure and analyse various factors affecting radiation exposure (RE) to surgeons during percutaneous nephrolithotomy (PCNL). Patients and Methods: A total of 212 patients who underwent PCNL were analysed. Informed consent was obtained from all enrolled patients. Ultrasonography/fluoroscopy guided punctures were done. The tract was dilatated and sheath placement done after which the procedure was completed in a routine fashion. A JJ or ureteric catheter or percutaneous nephrostomy (PCN) tube was placed as per the merit of the case. A digitalised mobile surgical C‐arm image‐intensifier system was used in all cases. RE was determined using a pen dosimeter worn outside the lead apron of the surgeon at the level of the chest for uniformity and was recorded on a per case basis at the end of the procedure. Data were recorded for analysis with respect to relevant parameters. Multivariate regression analysis was used to identify various parameters which affect RE (mSv). Results: The parameters analysed included: age, number and size of stones, body mass index (BMI) of patients, Hounsfield unit of stone (HU), degree of hydronephrosis, number of tracts, mode of access to pelvicalyceal system (PCS), sheath size (F), operative time (min), placement of a JJ or ureteric catheter or PCN tube, and kV used for exposure. There was a significant statistical relationship between stone volume ( P < 0.001), number of tracts ( P < 0.001), mode of access to PCS ( P = 0.001), and sheath size ( P = 0.002), with RE. The HU had a negative relationship, with a decrease in HU causing increased RE ( P = 0.002). BMI, number of stones, degree of hydronephrosis, operative time and placement of a JJ or ureteric catheter or PCN tube did not have any correlation with RE in our study. Conclusion: The mean (SD) RE per procedure was 0.21 (0.11) mSv. Increasing size and low HU of stone, increasing number of tracts, fluoroscopic access to PCS, increasing sheath size and kV were found to increase RE. Although the exposure levels are within safety limits, serial monitoring and constant vigilance are mandatory to inform surgeons.